Nitrogen requirement of fingermillet (Eleusine coracana)+ pulse intercropping system - R.V. SlNGH; M.P.S. ARYA (Indian Journal of Agronomy, 2001)
A field experiment was conducted during rainy (kharif) season of 1995 and 1996 under rainfed conditions to study N requirement of fingermillet [Eleusine coracana (L.) Gaertn.] + pulse intercropping system. Three levels of N (50, 75 and 100% of recommended,dose) were tested in fingermillet intercropped with each of soybean [Glycine max (L.) .) Marechal] and French Merr.], rice bean [Vigna aconitifolia (Jacq bean or rajma (Phaseolus radiatus L.). The highesttotal grain yield (28.64 qlha) was obtained under finger millet + soybean with 75% application. The land-equivalent ratio (1.31), fingermillet-equivalent yield (33.71 qlha), net return (Rs 6,892lha) and benefit : cost ratio (2.12) were also recorded higher in the same treatment.